Estimate of 3D power wall loads due to Neutral Beam Injection in EU DEMO ramp-up phase. (January 2019) - Vincenzi, P.; Varje, J.; Agostinetti, P.; Artaud, J.F.; Bolzonella, T.; Kurki-Suonio, T.; Mattei, M.; Sonato, P.; Vallar, M.
Highlights: NBI usability in DEMO1 ramp-up phase may be barely possible at low plasma density. NBI shine-through losses can exceed the tolerable first wall heat flux limit. Up to 29% shine-through losses (peak power of 1.1 MW/m 2 ) are found during ramp-up. With ITER criteria, DEMO NBI could be switched on in ramp-up at < ne > ∼ 1.3 × 10 19  m −3 . DEMO NBI operational window can be therefore enlarged to ramp-up phase. Abstract: Heating and current drive systems such as high energy Neutral Beam Injection (NBI) are being considered for pulsed EU DEMO ("DEMO1") pre-conceptual design. Their aim is to provide auxiliary power, not only during flat-top, but also during transient phases (i.e. plasma current ramp-up and ramp-down). In this work, NBI fast particle power loads on DEMO1 first wall, due to shine-through and orbit losses, are calculated for the diverted plasma ramp-up phase. Numerical simulations are performed using BBNBI and ASCOT Monte Carlo codes. The simulations have been done using a complete 3D wall geometry, and implementing the latest DEMO NBI design, which foresees NBI at 800 keV particle energy. Location and power density of NBI-related power loads at different ramp-up time steps are evaluated and compared with the maximum tolerable heat flux taken from ITER case. Since NBI shine-through losses (dominant during low density phases) depend mainly on the beam energy, plasma density and volume, DEMO has a more favourable situation than ITER, enlarging NBI operational window. Using ITER criteria, DEMO NBI at full energy and power could be switched on during ramp-up at e > ~ 1.3 × 10 19 m -3 . This increases the appeal of neutral beam injectors as auxiliary power systems for DEMO.